Pengaruh Social Media dan Kualitas Produk terhadap Repurchase Intention Melalui Kepuasan Pelanggan pada UMKM Alfahmi Konveksi - Mawaddah, Wirda; Rini, Endang Sulistya; Sembiring, Beby Karina Fawzeea (J-MAS (Jurnal Manajemen dan Sains), 2024)
This research aims to know the impact of social media and product quality on repurchase intention through customer satisfaction at UMKM Alfahmi Konveksi. The research method in this research is the quantitative method. The location of the research was carried out at Alfahmi Konveksi located at Rahmad PIK Complex No. A 42 Menteng VII, Medan Tenggara, Kec. Medan Denai, Kota Medan, North Sumatra 20226. As for the results of the research, it was found that (1) there was a positive and significant influence of social media on repurchase intention in UMKM Alfahmi Konveksi. (2) there is a positive influence and significant impact of product quality on repurchasing intention. (3) Colabored between social media and product quality have a positive, significant impact on repurchase intention through customer satisfaction. The findings provide a deep understanding of the importance of the role of social media and product quality in improving repurchase intention through customer satisfaction at UMKM Alfahmi Konveksi.